Implementation of the Use of Think Pair Card Media to Improve the Reading Skills of Yellow Books of Female Students of Class VI of Darul Falah Elementary School, Seputih Banyak, Central Lampung - Fadhila Nur Sa'adah; Hernisawati, Hernisawati; M. Sayyidul Abrori (Journal of Research in Islamic Education, 2025)
This study aims to implement the use of Think Pair Card media in improving the skills of reading yellow books at the Darul Ulum Islamic Boarding School, Seputih Banyak, Central Lampung. Yellow books are classic literature that are one of the main sources in Islamic boarding school education, but students often have difficulty understanding them. Through the use of the Think Pair Card method, it is hoped that students can more easily understand the contents of the yellow books in an interactive and collaborative way. This study uses a qualitative approach with observation, interview, and documentation methods. The results of the study indicate that the Think Pair Card method is effective in improving the skills of reading yellow books, where students are more active in discussing, able to identify problems better, and improve their understanding of the material. In addition, students feel more confident in expressing their opinions after discussing with their partners. Thus, the implementation of this Think Pair Card media can be used as an alternative method in learning in Islamic boarding schools to improve reading and understanding skills of yellow books.